The Crisis in the Financial Sector and the Authorities' Reaction : The Case of the Philippines - Nascimento, Jean-Claude (IMF Working Papers; Working Paper ;, 1990)
The paper discusses the crisis in the Philippines financial sector that began on a limited scale in 1981 and culminated in a significant contraction of the financial system in 1986. The causes, manifestation and transmission mechanism of the crisis are analyzed and reactions of the authorities to the crisis are examined. The main conclusion is that weaknesses of the regulatory framework and loose banking practices provoked and exacerbated the crisis, while the political and economic climate during 1979-83 also played a key role. In the end, the authorities' interventions to contain the crisis was sucessful but costly.